Decision-Making Processes in Community-based Free/Libre Open Source Software Development Teams with Internal Governance: An Extension to Decision-Making Theory - Eseryel, U. Yeliz; Kangning Wei; Kevin Crowston (Communications of the Association for Information Systems, 2020)
FLOSS teams are an extreme example of distributed teams, prominent in software development. At the core of distributed team success is team decision-making and execution. The lack formal organizational structures to guide practices and the reliance on asynchronous communication might be expected to make decision making problematic. While there is a paucity of research in how organizations make IS development decisions, the research in FLOSS decision making models is limited. Decision-making literature in FLOSS teams is limited to the investigation of the distribution of decision-making power. Therefore, it is not clear which decision-making theories fit FLOSS context best, or whether novel decision-making models are required. Despite these challenges many FLOSS teams are effective. We adopted a process-based perspective to analyze decision-making in five community-based FLOSS teams. We identified five different decision-making processes, indicating FLOSS teams use multiple processes when making decisions. Decision-making behaviors were stable across projects despite different type of knowledge required. We help fill in the literature gap due to the lack of investigations the extent to which FLOSS decision mechanisms can be explained using classical decision-making theories. Practically, community and company leaders should use these decision processes to infrastructure that fits best with the FLOSS decision-making processes.